The Influence of Knowledge, Skills, Attitudes, and Behavior on the Sustainable Performance of Vegetable Farmers from the Perspective of Sustainable Development Goals (SDGs) (A Study of Vegetable Farmers in Napu, North Lore District Poso Regency) - Ali Akrab; Wahyu Prianto (Postgraduate, University of Mataram, 2026)
This study aims to analyze the influence of knowledge, skills, attitudes, and behaviors on the sustainable performance of vegetable farmers from the perspective of the Sustainable Development Goals (SDGs) in Napu, North Lore District, Poso Regency. Farmers’ sustainable performance is a crucial indicator in supporting agricultural development oriented toward economic, social, and environmental sustainability. The research method employed was a quantitative approach using a survey technique. Data were collected by distributing questionnaires to vegetable farmers. The data analysis technique used was multiple linear regression to determine the influence of independent variables (knowledge, skills, attitudes, and behavior) on the dependent variable (sustainable performance). The results of the study indicate that knowledge, skills, attitudes, and behavior simultaneously have a significant influence on the sustainable performance of vegetable farmers. Partially, knowledge and skills have a positive and significant effect, while attitudes and behavior also positively influence sustainable performance. These findings indicate that enhancing farmers’ capacity through education, training, and behavioral change is crucial to achieving SDG goals, particularly in food security, sustainable agriculture, and farmer well-being. The implication of this research is the need to strengthen extension and mentoring programs for farmers to improve human resource quality and encourage the adoption of sustainable agricultural practices.